Acuacul- galeria de comercio y producción de materia prima vegetal (2021)
Project located in the municipality of Flandes Tolima, which is located within the Girardot-Ibagué-Cajamarca corridor, which has an environmental problem due to the extensive conventional agriculture crops that generate deforestation, greater probability of erosion, infertile soil and loss of biodiversity Therefore, the main objective is the recovery of the natural environment of the corridor through a succession of projects that strengthen the new cultivation mechanisms that promote regional and national development.